Поширення діаспор гідрофітів у зв’язку с проблемами синантропізації - Чорна, Г.А. (Промышленная ботаника, 2006)
The article gives principal means of generative diaspores of hydrophytes and helophytes distribution: hydrochory, anemochory, epizoochory, etc. It was determined, that for most species of ponds and bogs flora inherent several means of distribution – polychory. For hydrophytes especially alien it was inherent also hydrochory distribution of vegetative diaspors – turions. Some alien of hydrophytes for instance – the neophyte Elodea nuttallii (Planch.) St. John get to natural ponds from aquarium culture.